2019
DOI: 10.1103/physrevb.99.214302
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic theory for the light-induced anomalous Hall effect in graphene

Abstract: We employ a quantum Liouville equation with relaxation to model the recently observed anomalous Hall effect in graphene irradiated by an ultrafast pulse of circularly polarized light. In the weak-field regime, we demonstrate that the Hall effect originates from an asymmetric population of photocarriers in the Dirac bands. By contrast, in the strong-field regime, the system is driven into a non-equilibrium steady state that is well-described by topologically non-trivial Floquet-Bloch bands. Here, the anomalous … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
142
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 166 publications
(150 citation statements)
references
References 66 publications
5
142
0
Order By: Relevance
“…Motivated by this theoretical prediction, McIver et al recently observed the light-induced anomalous Hall effect in graphene under the presence of a circular laser field [27]. Soon after, we have theoretically investigated the microscopic origin of the observed light-induced anomalous Hall effect by the quantum Liouville equation with phenomenological dissipation [28]. As a result, we clarified that the imbalance of photocarrier distribution of topological Floquet states in the Brillouin zone predominantly causes the light-induced anomalous Hall current with a small contribution from the emergent Berry curvature of the Floquet states.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…Motivated by this theoretical prediction, McIver et al recently observed the light-induced anomalous Hall effect in graphene under the presence of a circular laser field [27]. Soon after, we have theoretically investigated the microscopic origin of the observed light-induced anomalous Hall effect by the quantum Liouville equation with phenomenological dissipation [28]. As a result, we clarified that the imbalance of photocarrier distribution of topological Floquet states in the Brillouin zone predominantly causes the light-induced anomalous Hall current with a small contribution from the emergent Berry curvature of the Floquet states.…”
Section: Introductionmentioning
confidence: 84%
“…Here, T 1 denotes the longitudinal relaxation time, which is responsible for the population decay, while T 2 denotes the transverse relaxation time, which is responsible for decoherence. According to [28], the relaxation times, T 1 and T 2 , are set to 100 fs and 20 fs, respectively. Here, we choose the longitudinal relaxation time…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In equilibrium materials, the origin of an anomalous Hall current can be unambiguously related to the Berry curvature structure, however in driven systems a careful analysis of the excitation process is required to relate an observed Hall current to the topological nature of the Floquet bands. Using the concept of Floquet fidelity, a measure of how well a given dynamical system is described by its corresponding Floquet states, the authors of [76] show that for the strong pump pulse intensities used in the experiment of [75], Floquet states are well established throughout the Brillouin zone (BZ) as shown in figure 3(d). The observed Hall current, however, is found to result not purely from the topology of the Floquet states, but is partly due to an imbalance in the population of excited states created by the pump.…”
Section: Experimental Observation Of Floquet Topological Phasesmentioning
confidence: 99%
“…Therefore, in experiments a delicate balance needs to be struck between the time necessary to establish the Floquet phase and the maximum time the material can sustain the radiation. In this context it is important to note that dissipative systems, where the energy can redistributed to a heat bath, can help to stabilize the Floquet phase [13,76,79]. In the next section, instead, we will explore the possibility to achieve establishing Floquet dressed states without the continued transfer of energy into the system.…”
Section: Experimental Observation Of Floquet Topological Phasesmentioning
confidence: 99%